ANALISA PENGEMBANGAN FASILITAS BANDAR UDARA PANGERAN ABDUL HAMID SEKAYU - Rosyad, Farlin; Wijaya, Rizky Putra; Firdaus, Firdaus; Irham, Irham (Ensiklopedia of Journal, 2024)
Prince Abdul Hamid Airport is an existing airport built in 2004, located in Musi Banyuasin district. Where the area of this district occupies 15% of the total area of South Sumatra province. The distance from the district capital to the city of Palembang is around ± 112 km or 3-4 hours by land, so the operation of this airport is expected to increase connectivity between regions and reduce travel time. By collaborating with aviation schools, a thorough arrangement and analysis of the needs for airside facilities and landside facilities is needed so that it can function as a flight school training airport. The research sample used was facility inventory data at Pangelran Abdull Hamid Airport. This research carried out qualitative improvements to airborne facilities and ground facilities based on existing estimates of the number of trainer aircraft and land available based on development policies, planning instructions and flight school student forecasts. As for the results of this research, it was found that the need for airside facilities related to the Largest Planned Aircraft, Aerodrome Reference Code (Runway 01-19), Runway Operational Category (Runway 01-19), Runway Dimensions (Runway 01-19), Runway Strip Dimensions (Runway 01-19), RESA (Runway 01-19), TURN PAD ( Runway 01-19), TORA (Runway 01-19), TODA (Runway 01-19), ASDA (Runway 01-19), LDA (Runway 01-19), APRON (Number of Parking Stands, Reserve aircraft, Apro Dimensions) , TAXIWAY (Existing Taxiway A, New Aviation College Taxiway). Then the need for land side facilities is related to the Campus Area, Flying School Terminal, Aircraft Maintenance Hangar, Hangar Support Building and also the PKP-PK Building.Keywords: Airport, Dimensions, Facilities, Aircraft, School